Miasto i jego ukryty wymiar w sztuce - Koniecko, Remigiusz (Wydawnictwo Naukowe UAM w Poznaniu; Wydawnictwo PWSFTViT w Łodzi, 2013)
The purpose of this article is to show the relationship between art, photography and architectural spaces that create new creative visions in these areas. The explored topic reveals a situation that affects the understanding of the current role of architecture, where previously there was no place for abstract concepts. Today this gap is complemented by artists as well as by architects, who often straddle architectural practice and a desire to be an artist. The penetration of these attitudes creates a situation in which the previously outlined boundaries of both disciplines are being crossed, in what might be called the transgression of art and architecture. As a result, a relationship between an artist and a given space is created. But what effect has this on the understanding of the relationship? What can we learn from these relationships?

Celem artykułu jest ukazanie relacji pomiędzy sztuką, fotografią i architektoniczną przestrzenią, które kreują nowe twórcze wizje w tych dziedzinach. Badany temat pokazuje także sytuację, która wpływa na pojmowanie dotychczasowej roli architektury, w której dotąd nie było miejsca na pojęcia abstrakcyjne. Dziś lukę tą uzupełniają artyści jak i sami architekci, którzy często pozostają na granicy praktyki architektonicznej i chęci bycia artystą. Przenikanie się tych postaw stwarza sytuację, w której zostają przekroczone dotychczas zarysowane granice obu dyscyplin, co można nazwać transgresją sztuki i architektury. W wyniku tego powstaje związek pomiędzy artystą, a daną przestrzenią. Ale jaki wpływ ma ten związek na pojmowanie przestrzeni? Czego możemy się dowiedzieć z tych wzajemnych relacji?
The City and its hidden dimension in art
Keywords: space; architecture; art; photography; transparency; przestrzeń; architektura; sztuka; fotografia; przezroczystość